Flood Disasters In Malaysia: Examining The Impact On Older People's Vulnerabilities And Rights - Nur Hamizah Amir Zaimi; Dina Imam Supaat (ZR RESOURCES, 2024)
International Journal for Studies on Children, Women, Elderly and Disabled, Volume 8, Page (240–246)